Evaluasi Pelaporan Keuangan Sistem ERP Odoo Community yang Dikembangkan PT Neo Multi Servindo - Vivian Chin; Hendro Lukman (Jurnal Ekonomi, 2022)
The purpose of this study is to evaluate whether financiing reports on the ERP system based on Odoo Community which has been developed by PT Neo Multi Servindo has provided the information needed for performance management. The object of this research is an ERP system based on Odoo Community which has been developed by PT Neo Multi Servindo. This type of research is a qualitative descriptive research by examining the subject and describing the facts found in the field. The result shows that financing reports on the ERP system based on Odoo Community already includes most of the information needed. Although, there is some information that is not yet available, the data regarding the required information can be found in a separate report. The implication of this research is that’s necessary to improve the completeness of information and visualization of financial reports so that better performance management can be achieved.